2013
DOI: 10.1103/physrevb.87.155206
|View full text |Cite
|
Sign up to set email alerts
|

Deep electron traps and origin ofp-type conductivity in the earth-abundant solar-cell material Cu2ZnSnS4

Abstract: Using hybrid functional calculation, we identify the key intrinsic defects in Cu2ZnSnS4 (CZTS), an important earth-abundant solar-cell material. The Sn-on-Zn antisite and the defect complex having three Cu atoms occupying a Sn vacancy are found to be the main deep electron traps. This result explains the optimal growth condition for CZTS, which is Cu-poor and Zn-rich as found in several recent experiments. We show that under the growth condition that minimizes the deep traps, Cu vacancy could contribute the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(25 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…As shown in several works [11][12][13][14], the deviations from stoichiometry in these materials influence critically their optical and electrical properties which ultimately define efficiencies. In the particular case of CZTS, it has been shown that the efficiency is improved for Cu-poor and Zn-rich thin films, i.e., films with a [Cu]/([Zn] + [Sn]) < 1 and [Zn]/[Sn] > 1 [15][16][17][18][19]. A similar trend was observed in Cu-poor CIGS [20][21][22][23].…”
Section: Introductionmentioning
confidence: 67%
“…As shown in several works [11][12][13][14], the deviations from stoichiometry in these materials influence critically their optical and electrical properties which ultimately define efficiencies. In the particular case of CZTS, it has been shown that the efficiency is improved for Cu-poor and Zn-rich thin films, i.e., films with a [Cu]/([Zn] + [Sn]) < 1 and [Zn]/[Sn] > 1 [15][16][17][18][19]. A similar trend was observed in Cu-poor CIGS [20][21][22][23].…”
Section: Introductionmentioning
confidence: 67%
“…Experimentally determined thermal activation energies are quite low 30-60 meV [3,4,5] compared to theoretical first principles calculations. These calculations [26,27], however, do not completely agree on the nature of the dominant defects and the level positions they introduce in the CZTS band gap. There seems to be a consensus that Cu Zn antisites (E a ≈ 120 meV [26], 220 meV [27]) and copper vacancies (V Cu , E a ≈ 20 meV [26], 70 meV [27]) are the dominant acceptor type defects, and that Zn Cu antisites (E a ≈ 150 meV [26], 70 meV [27]) and Cu interstitials (Cu i , E a ≈ 150 meV [26], 50 meV [27]) form rather shallow donors.…”
Section: Discussionmentioning
confidence: 84%
“…The Cu 2 ZnSnS 4 (CZTS) quaternary compound is widely discussed over the last few years as an active layer in thin films photovoltaic devices1234567891011. Although the electronic properties of the CZTS-heterojunction solar cells have been studied extensively the knowledge of the CZTS basic properties is still limited.…”
mentioning
confidence: 99%
“…Although the electronic properties of the CZTS-heterojunction solar cells have been studied extensively the knowledge of the CZTS basic properties is still limited. Particularly, the crystal structure412, intrinsic optoelectronic5689131415 and electrical properties9101617 are not well understood. The development of photovoltaic technologies based on this semiconductor strongly requires for the availability of experimental techniques suitable for the analysis of the crystalline quality of the CZTS absorbers.…”
mentioning
confidence: 99%